Comparative In Vitro Study of Sol–Gel-Derived Bioactive Glasses Incorporated into Dentin Adhesives: Effects on Remineralization and Mechanical Properties of Dentin - In-Seong Park; Hyun-Jung Kim; Jiyoung Kwon; Duck-Su Kim (Journal of Functional Biomaterials)
To overcome limitations of dentin bonding due to collagen degradation at a bonded interface, incorporating bioactive glass (BAG) into dentin adhesives has been proposed to enhance remineralization and improve bonding durability. This study evaluated sol–gel-derived BAGs (BAG79, BAG87, BAG91, and BAG79F) and conventional melt-quenched BAG (BAG45) incorporated into dentin adhesive to assess their remineralization and mechanical properties. The BAGs were characterized by using field-emission scanning electron microscopy (FE-SEM) and transmission electron microscopy for surface morphology. The surface area was measured by the Brunauer–Emmett–Teller method. X-ray diffraction (XRD) analysis was performed to determine the crystalline structure of the BAGs. Adhesive surface analysis was performed after approximating each experimental dentin adhesive and demineralized dentin by using FE-SEM. The elastic modulus of the treated dentin was measured after BAG-containing dentin adhesive application. The sol–gel-derived BAGs exhibited larger surface areas (by 400–600 times) than conventional BAG, with BAG87 displaying the largest surface area. XRD analysis indicated more pronounced and rapid formation of hydroxyapatite in the sol–gel BAGs. Dentin with BAG87-containing adhesive exhibited the highest elastic modulus. The incorporation of sol–gel-derived BAGs, especially BAG87, into dentin adhesives enhances the remineralization and mechanical properties of adhesive–dentin interfaces.